2005
DOI: 10.4067/s0717-93082005000400007
|View full text |Cite
|
Sign up to set email alerts
|

Paleoradiologia: Estudio Imagenologico Del Niño Del Cerro El Plomo

Abstract: Objectives: To describe the imagenologic findings of the «Niño del Cerro El Plomo» mummy. To check preservation status and look for clues of disease and make death related findings using a multisistemic evaluation and describe anthropometric features. Methods: A whole body multislice CT scan was done, followed by multiplanar reconstructions. We did an exhaustive analysis of internal organs. Results: The mummy is in a fetal position. The musculoskeletal system is well preserved. The age was estimated by the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
4
0
3
Order By: Relevance
“…Paralelamente, Sanhueza et al (2005) agregan que en el estudio imagenológico del cuerpo llama la atención la presencia de imágenes múltiples de linfonodos axilares que hipotéticamente podrían estar en relación a la presencia de alguna enfermedad infecciosa o parasitaria. La gran pregunta a resolver e investigar es cómo ocurrió la contaminación, dado que según registros epidemiológicos y de fauna silvestre la Trichinella sp.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Paralelamente, Sanhueza et al (2005) agregan que en el estudio imagenológico del cuerpo llama la atención la presencia de imágenes múltiples de linfonodos axilares que hipotéticamente podrían estar en relación a la presencia de alguna enfermedad infecciosa o parasitaria. La gran pregunta a resolver e investigar es cómo ocurrió la contaminación, dado que según registros epidemiológicos y de fauna silvestre la Trichinella sp.…”
Section: Discussionunclassified
“…Probablemente, el Niño del Cerro El Plomo fue ofrecido en sacrificio a los dioses cuando sólo tenía unos 8 a 9 años de edad, ésta calculada según el grado de desarrollo de las piezas dentarias (Sanhueza et al 2005). Al momento del hallazgo, se encontraron entre otros utensilios, mocasines de cuero, ajuares y finas ofrendas de plata entre las que destacan dos llamas y una estatuilla femenina ricamente ataviada (Cabezas 1986).…”
Section: Materiales Y Métodosunclassified
“…This may have been the case for the Llullaillaco children, as radiographs revealed air trapped in their lungs (Previgliano et al, 2003). The El Plomo boy and the two girls from Esmeralda may also have suffocated following inhumation (Sanhueza et al, 2005;Ojeda, 2012). In this scenario, the children would likely have been sedated or unconscious when buried (Previgliano et al, 2003).…”
Section: Cause Of Deathmentioning
confidence: 97%
“…Additionally, no Harris lines were observed on any of the children (Previgliano et al, 2003). Assessments of the El Plomo boy and the girls from Esmeralda also concluded that they were in good nutritional health (Sanhueza et al, 2005;Ojeda, 2012). Nutritional status may be used as a proxy for social status; it is assumed that children from higher classes would have consumed a more varied diet.…”
Section: Diet and Nutritionmentioning
confidence: 99%
“…The next discovery was also made by looters: a mummy of a boy of around eight years old was found on the summit of el Plomo in Chile (Sanhueza et al 2005). The mummy and part of the funeral assemblage were donated to the Museo Nacional de Historia Natural in Santiago.…”
Section: History Of Capacocha Discoveriesmentioning
confidence: 99%